6t=96

Simple and best practice solution for 6t=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t=96 equation:



6t=96
We move all terms to the left:
6t-(96)=0
We move all terms containing t to the left, all other terms to the right
6t=96
t=96/6
t=16

See similar equations:

| 4n-2=44 | | 14-8m=-13-5m | | |3x+5|+10=7 | | -5-9x=3-(2-3x)-8 | | 2y+0.9=-1.04 | | 8(2x-5)-4x=-10+7x | | 4(b-65)=76 | | -342=-9x | | -x+3=4x-17/ | | 4x-8=10x-2 | | −4x+3=23. | | 1=3n | | 2(m-4)=8+2m | | a-1.7=-4.9 | | 23x-3=17 | | 2p-10=32 | | 4(4x-7)-5=16x-33 | | X^2+6x-7=x+3+5 | | 4=g/10 | | 2/3t-5=2 | | 33-(2c+3=2(c+5)+c | | t+22=6 | | -3z+-7=2 | | b/3-8=-4.5 | | -b+2(-3b+8)=23-6b | | r+-6=1 | | 5=1/4x+2 | | -9h=-10h+18 | | -1=x/4+7 | | 2y=-61+5(5y+3) | | -4m+7=m-18 | | 5(5t+1)=25t-7+12 |

Equations solver categories